Fine Needle Aspiration Cytology of Thyroid Gland in Tertiary Care Unit - Humera Shahzad, Noshaba Rahat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of our study was to determine the reliability of preoperative FNAC diagnosis of thyroid gland swelling in pathology Department BMSI, JPMC (Jinnah Postgraduate Medical Centre) Karachi. Study design & place: cross-sectional study was conducted at Pathology BMSI, JPMC during January 2022 to 30th June 2022. Material and Methods: Total 200 patients of thyroid FNA aspiration cytology were evaluated in FNA OPD All smears and cellblock stained with eosin and hematoxylin. Data was analyzed by using Statistical Package for Social Sciences version 25 (SPSS 25). Results: FNAC findings were classify as benign,malignant ,cystic and inflammatory lesions. Out of 200 cases,173 patients were female and 27 were male(female to male ratio was 8.9:1.68) .all cases were diagnosed according to Bethesda system .and benign lesions predominantly hyperplasia followed by cystic lesion were commonest finding .5 neoplastic lesions and one metastatic lesion Conclusion: Hyperplasia and benign lesion with cystic changes are commonest finding and predominant in females suggestive of neoplastic lesions are helpful for treatment plan of patients. Keywords: FNAC Fine needle aspiration cytology JPMC Jinnah Postgraduate Medical Centre Hyperplasia cystic lesion metastatic carcinoma